2012
DOI: 10.1155/2012/362536
|View full text |Cite
|
Sign up to set email alerts
|

Does Cisapride, as a 5HT4Receptor Agonist, Aggravate the Severity of TNBS-Induced Colitis in Rat?

Abstract: There is a pressing need for research that will lead to the reveal of targets designed to analyse the possible pathways for the treatment of IBD. Because of the probable involvement of serotonin in inflammatory conditions of intestine and the important role of 5HT4 receptors in GI function, the investigation of the role of 5HT4 receptors in the pathogenesis of IBD will be interesting. The aim of this study was to investigate the effects of cisapride, a 5HT4 receptor agonist, in trinitrobenzenesulfonic-acid-(TN… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…MPO activity is an important index of neutrophil influx in inflamed tissues of intestine (2530). We found that the ability of alosetron in decreasing neutrophil infiltration was due to suppressed MPO activity in colon.…”
Section: Discussionmentioning
confidence: 99%
“…MPO activity is an important index of neutrophil influx in inflamed tissues of intestine (2530). We found that the ability of alosetron in decreasing neutrophil infiltration was due to suppressed MPO activity in colon.…”
Section: Discussionmentioning
confidence: 99%
“…Then paraffin sections were deparaffinized with xylene and then hydrated and stained with hematoxylin and eosin (H&E). The stained sections were assessed for any inflammatory changes including infiltration of cells, necrosis, or damage to tissue structures [ 31 ]. Inflammation severity and extent as well as crypt damage were evaluated on H&E stained according to the criteria previously described by Dieleman et al [ 32 ].…”
Section: Methodsmentioning
confidence: 99%
“…Cisapride monohydrate (Sigma-Aldrich) was dissolved in vehicle (10% dimethyl sulfoxide; Sigma-Aldrich). Urethane (20%, 0.8 g/kg) and cisapride (0.2, 0.02, and 0.002 mg/kg) [ 11 13 ] were used in separate cohorts of rats.…”
Section: Methodsmentioning
confidence: 99%